Autonomy and family business performance: The joint effect of environmental dynamism and national culture. (March 2019) - Yu, Andy; Lumpkin, GT; Praveen Parboteeah, K; Stambaugh, Jeffrey E
Building on the entrepreneurial orientation (EO) literature, we investigate the relationship between family firm performance and autonomy, a key EO dimension. To enhance the understanding of the role of autonomy, we compare the joint impact of environmental dynamism and national cultural context (performance-based vs socially supportive cultures) on the autonomy–performance relationship of family firms in the United States and Taiwan. Using a configurational approach and data from 130 family firms (53 in the US and 77 in Taiwan), we found that in dynamic environments, autonomy is associated with improved performance in the United States, while in Taiwan, firms in dynamic environments fared worse with increasing autonomy. We discuss the implications of these findings and provide recommendations for future research.